The Effect of Auxiliary Energy on Rhein, Kaempferol and Astragalin Extraction from Cassia Alata - Yeong, Yi Ling; Pang, Sook Fun; Jolius, Gimbun (EDP Sciences, 2017)
This paper presents the effect of auxiliary energy on rhein, kaempferol and astragalin extraction from Cassia alata. The effect of auxiliary energy was examined by performing extraction using either the ultrasonic assisted extraction (UAE) or microwave assisted extraction (MAE). A dried plant material with size ranging from 125 μm to 800 μm was used throughout this work. The rhein, kaempferol and astragalin quantification and identification was performed using ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometer. The presence of rhein, kaempferol and astragalin were identified and compared with external standards.The residence time, neutral mass and mass fragmentationpattern between the standard and plant extract are also observed. It was found that the extraction yield of rhein, kaempferol and astragalin were higher with UAE method compared to MAE method due to degradation of active component occur. The findings in this work may serve as a useful guide to select the extraction method used to maximise the yield of rhein, kaempferol and astragalin extraction from C. alata.